A Q-matrix Model Based on Binarized Neural Network. Issue 1 (1st January 2022) - Li, Jingjiang; Jiang, Chong; Ye, Shiwei
Abstract: Q-matrix theory plays an important role in the field of cognitive diagnosis assessment. It is time-consuming and laborious for experts to define Q-matrix from a large number of data. In order to deal with this problem, this article comes up with a Q- matrix generation model based on binarized neural network. We combine the neural network with the Boolean operation relations of Q-matrix, A matrix and R matrix in item response theory, so that the model can mine Q-matrix more effectively.